2021
DOI: 10.1002/humu.24290
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of patient‐specific NF1 variants leads to functional insights for Ras signaling that can impact personalized medicine

Abstract: We have created a panel of 29 NF1 variant complementary DNAs (cDNAs) representing missense variants, many with clinically relevant phenotypes, in-frame deletions, splice variants, and nonsense variants. We have determined the functional consequences of the variants, assessing their ability to produce mature neurofibromin and restore Ras signaling activity in NF1 null (−/−) cells. cDNAs demonstrate variant-specific differences in neurofibromin protein levels, suggesting that some variants lead to neurofibromato… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 37 publications
3
10
0
Order By: Relevance
“…1 B ) in NF1 knockout 293T cells. This is consistent with previous reports of lower mutant protein expression observed in a G848R mouse model of NF1 ( 13 , 14 ) and in cells transiently expressing mouse Nf1 cDNA (complementary DNA) with L847P and G848R ( 15 ). Despite lower levels of expression, these mutants are still able to form heterodimers with wild-type protein ( Fig.…”
Section: Resultssupporting
confidence: 93%
“…1 B ) in NF1 knockout 293T cells. This is consistent with previous reports of lower mutant protein expression observed in a G848R mouse model of NF1 ( 13 , 14 ) and in cells transiently expressing mouse Nf1 cDNA (complementary DNA) with L847P and G848R ( 15 ). Despite lower levels of expression, these mutants are still able to form heterodimers with wild-type protein ( Fig.…”
Section: Resultssupporting
confidence: 93%
“…There is a disconnect between the level of full-length transcript generated upon PMO treatment, and the amount of neurofibromin protein produced in the cell. Based on recently published data, mNf1 cDNA containing the Y489C missense mutation was able to produce a stable protein product [8], and thus, we suspect that this disconnect is not the result of a protein stability issue, but rather some other mechanism.…”
Section: Discussionmentioning
confidence: 82%
“…Previously, we created a cDNA of this variant (Y489C) that was not subject to splicing and showed that the missense variant alone did not disrupt Ras signaling [7]. More recently, we have shown that the variant had no effect on neurofibromin's expression, indicating that if the aberrant splicing could be corrected, the missense variant may not be deleterious [7,8]. Hence, a PMO approach might be feasible as a treatment strategy.…”
Section: Introductionmentioning
confidence: 99%
“…One potential dominant-negative mechanism represents dimerization of mutant and WT neurofibromin [53,54] , with resultant degradation of WT neurofibromin at the faster rate of the mutant [110] . In this scenario, an NF1-HCT approach that decreases neurofibromin degradation may be preferable to one that increases NF1 transcription.…”
Section: Implications For Nf1-hctmentioning
confidence: 99%